Epidemiology of abusive abdominal trauma hospitalizations in United States children - Lane, Wendy Gwirtzman (2012)
OBJECTIVES: (1) To estimate the incidence of abusive abdominal trauma (AAT) hospitalizations among US children age 0–9 years. (2) To identify demographic characteristics of children at highest risk for AAT. DESIGN: Secondary data analysis of a cross-sectional, national hospitalization database. SETTING: Hospitalization data from the 2003 and 2006 Kids' Inpatient Database (KID). MAIN EXPOSURE: Frequency and rate of hospitalizations for abusive abdominal trauma as identified by ICD-9CM codes for abdominal trauma and child abuse and E-codes for inflicted injury. OUTCOME MEASURES: Hospitalization rates by age, insurance status, and frequency of specific organ injury. RESULTS: AAT rates were higher for infants than for any other age group, with 17.7 (95% CI 11.7–23.9) cases per million in 2006. More than 25% of all abdominal trauma in children <1 year of age was abusive. For all age groups, rates were higher for males than females, and for children insured by Medicaid compared to those with private insurance. Organs most commonly injured were the liver (64% of hospitalizations), kidney (19%), and stomach/intestines (12%). CONCLUSIONS: Although experts have considered toddlers to be at highest risk for AAT, infants have higher rates of AAT hospitalization. Similar to other abusive injuries, young age, male gender, and poverty are risk factors for AAT.